The Family of Francis Marion Shaw Newsletter Volume 20 Number 2 - Shaw, Bryan Lee (My University, 2013)
This newsletter primarily profiles Ida Lena Knight Hickman, a granddaughter of Francis Marion Shaw, detailing her life as a farmer's wife alongside her husband, Edgar Hickman. Lena's early life was marked by hardship, including her family's home burning down and her father's sudden death, which led her mother and younger sisters to live with their grandparents, Francis Marion and Rachel Shaw. She married Edgar Hickman at just 15, drawn by his "fancy buggy and beautiful horse," and together they navigated the challenges of farming, initially living with his parents and later struggling as sharecroppers for over two decades after Edgar lost his own farm. Lena diligently raised their children and, once her youngest started school, began working, first managing the cafeteria at Barney school and later overseeing a staff of five or six at Morven school until a heart attack forced her retirement in 1964. The couple eventually purchased their own home in Barney in 1951, and Edgar continued to farm garden crops. Their lives were deeply rooted in their family and community, particularly through their active membership at Friendship Baptist Church, until Edgar's death in 1968 and Lena's in 1977.
This item contains 1 PDF file with 4 pages in addition to 4 JP2 files
Keywords: Berrien County (Ga.); Berrien County Historical Foundation (Nashville; Ga.); Nashville (Ga.); Newsletters; Periodicals; Berrien County (Ga.)--History--Sources; Electronic records; Grady County (Ga.)--History; Historic preservation--Georgia--Berrien County; Georgia--Genealogy